Sustainable Tourism Practices and Their Impact on Local ‎Communities in Tamil Nadu - Rajha, R A Dhilipan; G, Rajini (International Journal of Accounting and Economics Studies, 2025)
Sustainable tourism has involved an important approach to balancing economic growth, social well-being, as well environmental ‎conservation, particularly in culturally and ecologically rich regions like Tamil Nadu. This study examines the implementation of sustainable ‎tourism practices and their effect on local communities, focusing on environmental sustainability, economic benefits, and socio-cultural ‎preservation. The research utilizes a mixed-method method they proceed, integrating quantitative surveys and qualitative interviews with key ‎stakeholders, including residents, tourists, and tourism industry professionals.‎ Findings indicate that sustainable tourism follow-up, such as community-based tourism initiatives, eco-friendly accommodations, and ‎heritage conservation efforts, contributes significantly to the local economy by generating placement and promoting rural businesses. ‎However, challenges such as over-tourism, inadequate policy enforcement, and environmental degradation remain prevalent. The research ‎points out the place of government policies and private sector involvement in fostering responsible tourism.‎ The research concludes that while sustainable tourism enhances the qualified local communities by preserving cultural heritage as well as ‎improving livelihoods, a collaborative effort between stakeholders is essential to address existing challenges. Strengthening regulatory ‎frameworks, promoting eco-tourism awareness, and ensuring equitable benefit distribution are crucial for achieving long-term sustainability ‎in Tamil Nadu’s tourism sector‎.